74 Hypermobility in young boys with duchenne muscular dystrophy and the effect on attainment of walking age and North star ambulatory assessment functional skills. (30th November 2020) - Abbott, Lianne; Selby, Victoria; Guptar, Vandana Ayyar; Wadsworth, Stephanie; Wolfe, Amy; Chesshyre, Mary; Baranello, Giovanni; Scoto, Mariacristina; Manzur, Adnan; Main, Marion; Muntoni, Francesco
Abstract : On average children with hypermobility achieve motor milestones later than peers without. This study looked at the prevalence of hypermobility in a sample of Duchenne Muscular Dystrophy (DMD) and aimed to determine if hypermobility has an impact on walking age and delays attainment of functional skills assessed by the North Star Ambulatory Assessment (NSAA). This is a retrospective study of 158 boys with DMD aged 3 to 8 years (±3 months). During clinical appointments each boy was assessed using the NSAA, joint ranges measured and age of walking noted. Hypermobility was determined using the revised Beighton scale where a score above 4 is considered hypermobile. The young DMD population had a higher percentage, 18%, of hypermobility compared to healthy controls, 7%. The pattern of hypermobility in DMD differed as well; knees and elbows were more commonly hypermobile compared to the expected ankles and thumbs. In DMD only 5% had hypermobile ankles compared to 22%. Hypermobility in DMD ankles often quickly tightened. Non hypermobile DMD boys walked on average at 17.8 mths (range 10–36 mths). This was similar to hypermobile boys; average 19 mths (range 13–36 mths). Hypermobile DMD boys were found to have a lower average NSAA at each age point than those who weren't hypermobile, approximately 6 months behind. Both DMD groups gained functional skills with increased age until 6.5 (non hypermobile) and 7 years (hypermobile). Both groups subsequently declined. Hypermobility is more common in DMD and impacts development of later functional skills, however doesn't dramatically influence age of walking started. Hypermobility should be therefore be considered when predicting the development of later skills. There are however other factors which can alter progression of NSAA including behaviour. More research is needed to further understand the impact of hypermobility in the DMD population especially for later years and loss of ambulation.